CONSTRUCTION OF AN INNOVATION MODEL FOR LOYALTY THROUGH CUSTOMER TRUST: ECO HILL RETREAT AND RESTO STUDY IN BALI - Meryawan, I Wayan; Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Idayanti, I Dewa Agung Ayu Eka; Suwandana, I Made Adi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
As a tourist destination, Kisidan Eco Hill Retreat and Resto is full of natural concepts, and local wisdom of ancient Balinese tourism and ecotourism on which tourism village products depends. However, the low level of innovation in products and services that exist today indicates weak trust and declining loyalty. Loyalty is an issues of problems faced by business industry players and has become a conversation among national and international business actors. Researchers will explore how strong the influence of innovation in increasing loyalty through current customers trust as a reference in the future. The study used an SEM test tool model with stages of descriptive analysis, inferential analysis and evaluation of goodness of fit PLS model. This research shows that customers trust is capable to completely mediate innovation on loyalty. The direct results of innovation is that it does not have any significance effect on loyalty and on the contrary innovation is capable to build trust and significant trust builds loyalty. The implication of this research in the context of Eco Hill and Resto tourism business, customer trust holds a strong roles to stimulate the creation of sustainable customers loyalty if built from innovation. Although innovation is built innovatively without gaining strong trust from customers, it has not been capable to stimulate loyalty.